1995
DOI: 10.3109/00016489509139344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostaglandins D, and E2on Ciliary Beat Frequency of Human Upper Respiratory Ciliain Vitro

Abstract: Diminished mucociliary transport can occur in a type-I (Ig-E mediated) allergic reaction. We determined the effects of the allergy mediators prostaglandin D2 (PGD2) and prostaglandin E2 (PGE2) on the ciliary beat frequency (CBF) of human upper respiratory cilia in vitro. Human adenoid tissue was used as the source for ciliated epithelium. CBF was measured by a computerized photo-electric method. PGD2 (10(-8)-10(-5) M, n = 7) showed no statistically significant effect on CBF. PGE2 (10(-9)-10(-6) M, n = 10) caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…32 Furthermore, prostaglandin E 2 has been shown to acutely decrease CBF. 33 In our study, CBF showed a statistically significant dose-dependent increase in the experimental group compared with the control group that persisted up to 24 hours.…”
Section: Discussionsupporting
confidence: 54%
“…32 Furthermore, prostaglandin E 2 has been shown to acutely decrease CBF. 33 In our study, CBF showed a statistically significant dose-dependent increase in the experimental group compared with the control group that persisted up to 24 hours.…”
Section: Discussionsupporting
confidence: 54%
“…Following a systematic literature review we identified cAMP (Di Benedetto et al, 1991; Haxel et al, 2001; Runer and Lindberg, 1999; Schmid et al, 2006), IL-5 (Grosse-Onnebrink et al, 2016), IFN-γ (Grosse-Onnebrink et al, 2016), Prostaglandin-E2 (Bonin et al, 1992; Haxel et al, 2001; Schuil et al, 1995) and Sildenafil (Fowler et al, 2020), as compounds previously shown to enhance human ciliary motility either via changes in calcium levels or through various signal transduction pathways. Xenopus tadpoles (stage 34) were pre-treated with the candidate compounds, at concentrations indicated in Figure 5 , and examined for their specific effects in mucociliary flow.…”
Section: Resultsmentioning
confidence: 99%
“…Other groups found a significant increase in CBF after exposure to different mediators related to inflammation. 16 Bonin, Phillips and McCaffrey 17 and Khan, Dolata and Lindberg 18 found that inflammatory substances (PGE 2 , prostacyclins) can upregulate CBF in respiratory cells. Substance P seems to have similar effects.…”
Section: Discussionmentioning
confidence: 99%